Curious2018 Future Insights in Science and Technology - Betz, Ulrich A.K (Springer International Publishing : Imprint: Springer, 2019)
This book expands the debate on the future of science and technology at the Curious2018 - Future Insight Conference, held on the occasion of Merck's 350-year anniversary. In the respective chapters, some of the world's top scientists, managers and entrepreneurs explore breakthrough technologies and how they can be applied to make a better world for humanity. Divided into three parts, the book begins with an introduction to the vision of the conference and to the importance of curiosity for innovation, while also exploring the latest scientific developments that are shaping the future of healthcare, medicine, the life and material sciences, digitalization and new ways of working together. In the second part, particular attention is paid to new therapies and diagnostics; here, readers will learn how synthetic biology and chemistry are being used to solve problems that are essential to the future of humanity. The role of in-silico research is also discussed.In the final part of the book, readers will find some thoughts on ethical principles guiding our application of science and technology to create a bright future for humanity. Given its interdisciplinary appeal, the book will inspire curiosity in a wide readership, from scholars and researchers to professionals with an interest in exploring the future of science and technology, solving the problems of today, and paving the way for a better tomorrow. Chapters 1, 2, 3 and 17 are available open access under a Creative Commons Attribution-NonCommercial 4.0 International License via link.springer.com. Book includes a foreword from J. Craig Venter.